Efficiency of foliar application of growth stimulators «4R Foliar concentrate» on barley spring crops - Штугеревич, В. С. (Scientific Progress & Innovations, 2018)
In the experiment, conducted in production conditions, the results were obtained, which testify to the rather high effectiveness of the use of drugs based on humic substances. The foliar application of the preparation «4R Foliar concentrate» (USA) in the norm of 1.5–2 kg/ha made it possible to substantially increase the yield of barley grain. On average, for three years of research spraying of crops contributed to an increase in yield by 11.4–22.8 % with a seeding rate of 4.5 million pieces of seeds per hectare. In case of a decrease in the norm to 4 million pcs. the yield of the control variant (without spraying) was somewhat smaller, but the increase in the yield level was 30.4 %. The processing of crops with «4R Foliar concentrate» helped increase the mass of 1000 grains by 1.1–4.2 g, depending on the seeding rate, and the grain size increased by 6–8 %. Seed seeding rates, which provide an average of 4.5 million pcs. of seeds per hectare can be inexpedient, since the difference between control options for yield is not significant, but a decrease of 0.5–1 million is economically justified. So, in the case of a decrease in seed sowing rates of 1 million pcs. of seeds per hectare, the yield is not changing significantly, but the profitability of production is growing by almost 10 %. Even in the case of high rates of sowing, the profitability of production is higher by 9–24 %.